Optical performance and chemical stability evaluation of new era phase change material: Activated by hybrid nanoparticle - Pandey A.K.; Kalidasan B.; Rajamony R.K.; George M. (Institute of Physics, 2024)
Inorganic salt hydrate phase change materials (PCMs) are ahead of organic PCMs in terms of energy storage ability and safety as they are non-flammable. However the major hindrance with inorganic PCM are degree of supercooling and low thermal conductivity though better than organic PCM. The common technique to enhance the thermal conductivity is via dispersion of metal and carbon nanoparticle. Though they enhance the thermal conductivity of the nanocomposite, with continuous operation the nanoparticle agglomerate and settles down owing to their density. Henceforth, in the current research work we conduct an experimental investigation to enhance the optical and thermal performance of commercialised inorganic salt hydrate PCM using metal-carbon hybrid nanoparticle. We disperse graphene silver nanoparticle at different weight ratio adopting a two-step method followed by probe sonication to ensure uniform dispersion. We achieve a highly stable nanocomposite with 584% increase in optical absorbance of electromagnetic waves and 86% decrease in transmittance. Thermal management of electronic gadgets has evolved to be a major consideration of research as overuse of gadgets lead to rapid temperature rise and is in need of passive cooling system. Henceforth the newly developed nanocomposite phase change materials (PCMs) not only acts as thermal batteries but can also be opted as energy materials for thermal regulation and heat mitigation. 2023 Institute of Physics Publishing. All rights reserved.